Using SEM (Structural Equation Modeling) to Examine the Effects of the Body's Image on what Women Like and Choose in Clothing - Berna Yildirim Artac; Fatma Koc (European Scientific Journal, ESJ, 2017)
For women the body is an important concept in clothing aesthetics. Body image is an important factor influencing what women like in clothing and what they choose to wear.In this study, which has been prepared with the aim of stressing the importance of the relationship between "Clothing Preference" and "Body Image", women's ability to minimize the difference between their ideal appearance and their actual appearance, as well as their ability to possess a good self-image and powerful self-confidence, have been studied.Structural Equation Modelling (SEM) was used in this study. The sample is 150 women aged 18-50 within the Konya Province in Turkey limits. The research concluded that while there was a relationship between the visual and verbal clothing choices for the women in the sample group, there was less of a match among their visual choices.